Escape to recovery. Discovering architectural innovations for mindful meditation with landscapes - Yang, Jihyun (School of Architecture, Planning and Geomatics, 2024)
The expansion and exploration of the interplay between architecture and landscape seeks to heal the disconnect between these two disciplines. The dissertation focuses on how the two aspects’ integration can provide tranquillity and solace amidst the modern urban environment. Existing as two separate identities, with all its natural beauty, Cape Town experiences this defined contrast. Buildings and complex infrastructure have severed humanity from their landscape, urging people to blend the constructed and the natural. Through the four fundamental concepts of landscape discovery by Christophe Girot, the exploration of a site nestled between the high urbanity of Cape Town and the serene suburbs of Hout Bay and Llandudno. The site offers a different perspective of tranquillity, something indifferent to the city experiences. The investigation proposes to develop and illustrate how nature can significantly impact human well-being. Spaces concentrating on rehabilitation incorporating the natural environment as a primary stimulant are introduced. Designing is the primary element of the inquiry and how spaces can be created to generate certain pauses and moments for the people to connect this relation between architecture and landscape. The design of the exterior spaces and pedestrian routes in between are carefully considered to enhance the people’s experiential value. The built form draws from the environment as it engages with the landscape